ANALISIS KERENTANAN KEJAHATAN ONLINE PHISING MENGGUNAKAN TOOLS ZPHISHER, SHELLPHISH DAN WHPHISHER: Phising - Wahyuni, Ni Komang Arista Tri; Putu Putri Cahayani; I Gusti Ngurah Yogi Wicaksana; Ida Ayu Kadek Bintang Wijayanti (Pusat Riset dan Inovasi Nasional, 2023)
In the era of increasingly advanced and widespread technology as it is today, personal data is an asset that really needs to be protected by an organization or individual, personal data information that is private is very important to be protected so that it cannot be accessed by unauthorized parties. Phishing attacks are currently still increasing, this happens because the perpetrators of phishing attacks understand to trick victims where the victim is still weak to understand the security system on personal data information. The purpose of this article is to explain how these phishing attacks can still be carried out, so that technology users can better understand phishing attacks and further improve the security of users' personal data themselves. Website phishing attack technique is one type of phishing attack that can be done with several types of tools including Zphisher, Shellphish and WhPhisher. With the exposure of this article, technology users get information regarding phishing website attacks and actions to deal with them. Keywords: website phishing, Zphisher, Shellphish, WhPhisher